The behavior of biologically important trace elements across the oxic/euxinic transition of meromictic Fayetteville Green Lake, New York, USA. (15th September 2015) - Havig, Jeff R.; McCormick, Michael L.; Hamilton, Trinity L.; Kump, Lee R.
Abstract: Trace elements are central components of enzymes that catalyze many of the essential reactions mediated by life. The redox sensitive nature of trace elements also permits their use as a record of ancient ocean conditions preserved in the geologic record. Trace element geochemistry in modern stratified systems is often used as a proxy for the redox state of the ancient oceans, which are thought to have been largely anoxic. In the present study, we examined trace element behavior of simultaneously collected samples at a heretofore unprecedented depth resolution (1–0.25 m intervals) throughout the redox-stratified water column of Fayetteville Green Lake, N.Y. (FGL), a 53 m deep meromictic lake under euxinic conditions similar to those thought to have been prevalent in Proterozoic oceans. Among characterized Proterozoic ocean analogs, FGL represents an understudied proxy in terms of trace elements, with characteristics of low salinity and high sulfate. In the FGL water column, spikes in the concentration of dissolved Mn, Fe and Co are coincident with the transition from oxic to euxinic conditions, and are associated with a decrease in dissolved Mo concentration. In contrast, the concentration of dissolved Ni did not vary across this transition despite the dramatic shift in redox state. From these data we present a one dimensional model for element transport and cycling through the water column to the sediments. Collectively, this comprehensive analysis of water column geochemistry provides insight into the effects of biogeochemical cycling in stratified systems on dissolved trace element concentrations in the water column. This study, in concert with characterization of other early Earth analogs, will greatly enhance the use of trace elements in interpreting the geologic record.